Collateral Damage: Ali Reynolds #17 : an Ali Reynolds mystery - Jance, Judith A. (New York : Gallery Books, 2023)
Ali Reynolds tries to figure out who was the real target and who was the collateral damage after her husband is forced off the road in an airport limo while preparing to fly to a ransomware conference in London.
new book 2023 spring.
Keywords: Reynolds, Ali -- (Fictitious character) -- Fiction; Women private investigators -- Fiction -- Arizona; Revenge -- Fiction; Spouses -- Fiction; Ex-police officers -- Fiction; Malware (Computer software) -- Fiction; Traffic accidents -- Fiction; Revenge; Women private investigators; Arizona; Detective and mystery fiction; Novels; Fiction; Thriller fiction; Detective fiction; Mystery fiction